Use of class IC antiarrhythmic drugs in patients with structural heart disease and implantable cardioverter defibrillator - Zylla, Maura Magdalena; Wolfes, Julian; Schleberger, Ruben; Lawin, Dennis; Kieser, Meinhard; Reinke, Florian; Eckardt, Lars; Rillig, Andreas; Stellbrink, Christoph; Thomas, Dierk; Frey, Norbert; Lugenbiel, Patrick (Clinical research in cardiology, 2024)
BACKGROUND: Due to suspected pro-arrhythmic effects and increased mortality associated with class-IC antiarrhythmic drugs (AADs) in previous trials, AAD therapy in structural heart disease (SHD) is mainly restricted to amiodarone. In the presence of diagnostic and therapeutic advancements in cardiovascular medicine, it remains unclear if previous studies adequately reflect contemporary patients. In clinical practice, class-IC-AADs are occasionally used in individual cases, particularly in patients with an implantable cardioverter defibrillator (ICD). - METHODS: This study retrospectively investigated outcome in ICD-carriers with SHD in whom class-IC-AADs were used as an individualized therapy due to failure, side effects, or unacceptable risk of alternative therapeutic options. - RESULTS: Fifty patients from four tertiary centers were included (median age 48.5 years; 52% female). The most common underlying SHD were dilated (42%) or ischemic cardiomyopathy (26%) (median LVEF = 45%). Indications for AAD were sustained ventricular arrhythmias (VA) (58%), symptomatic premature ventricular contractions (26%), or atrial arrhythmias (16%). Median follow-up was 27.8 months. Freedom from sustained VA was 72%, and freedom from ICD therapy was 80%. In 19 patients (38%), AAD therapy was terminated. The most common reason was insufficient efficacy (n = 8). Pro-arrhythmia was suspected in three patients. Five patients died during follow-up (10.0%), two of cardiovascular cause (4.0%). - CONCLUSION: In a multicenter cohort of ICD-carriers with SHD, class-IC-AADs were associated with a low rate of pro-arrhythmic effects or cardiovascular mortality. The majority of patients remained free from sustained VA during a follow-up of > 2 years. Further efforts should be made to evaluate the safety of class-IC-AADs in SHD patients receiving contemporary cardiovascular therapy.
Gesehen am 06.08.2024